11-Beta-Hydroxylase Deficient Congenital Adrenal Hyperplasia in a Toddler: Clinical Presentation and Management Challenges in a Developing Country - Onyiriuka, AN; Shaibu, M (Journal of Nepal Paediatric Society, 2013)
This paper reported a case of an eighteen-month old Nigerian girl with 11-beta-hydroxylase-deficient congenital adrenal hyperplasia who presented with hypertension and heart failure. The hypertension resolved with steroid therapy. Her blood pressure has remained normal on maintenance prednisolone. The abnormal external genitalia was probably missed at the private hospital where the child was born as it was not mentioned to the parents before discharge on the second day of life. When the child presented at about the age of two months with an enlarged clitoris, she was referred to a paediatric surgeon in another private hospital. It would have been more appropriate to refer her to a paediatric endocrinologist in the nearest tertiary healthcare institution. This case highlights the importance of thorough physical examination of the external genitalia at birth and appropriate referral. The management challenges encountered in the care of this patient included lack of laboratory facilities for diagnosis and monitoring of therapy, non-availability of necessary drugs (oral hydrocortisone) and late presentation. DOI: http://dx.doi.org/10.3126/jnps.v33i1.6181 J Nepal Paediatr Soc. 2013;33(1):48-51